Cortical hyperexcitability evolves with disease progression in ALS. Issue 5 (18th April 2020) - Menon, Parvathi; Higashihara, Mana; van den Bos, Mehdi; Geevasinga, Nimeshan; Kiernan, Matthew C.; Vucic, Steve
Abstract: Objective: Cortical hyperexcitability has been established as an early feature of amyotrophic lateral sclerosis (ALS). The evolution of cortical hyperexcitability with ALS progression remains to be fully elucidated. This study aims to investigate changes in cortical function in ALS with disease progression. Methods: Cortical function assessed by threshold tracking transcranial magnetic stimulation (TMS) along with clinical phenotyping was prospectively undertaken on 444 patients presenting with suspected ALS (345 ALS; 99 neuromuscular mimics). Disease stage was defined as follows: (1) King's clinical staging system and (2) proportion of disease duration statistically categorized into tertials. Results: Cortical hyperexcitability was evident across all ALS stages, being more prominent in later stages of ALS as indicated by increased motor‐evoked potential amplitude ( P < 0.05), as well as longer disease duration as reflected by reduced short‐interval intracortical inhibition ( P < 0.05). Prolonged central motor conduction time was evident with disease progression. These changes were accompanied by reduction in neurophysiological index ( P < 0.001) and compound muscle action potential amplitude ( P < 0.01), progressive muscle weakness ( P < 0.001), and decline in the ALS functional rating scale ( P < 0.001). Interpretation: This study established an increase in cortical hyperexcitability with increased disease duration in ALS, mediated by cortical disinhibition and direct increase in corticomotoneuronal excitability.